Post Meal Exercise May Lead to Transient Hypoglycemia Irrespective of Glycemic Status in Humans - Porter, Jay W.; Pettit-Mee, Ryan J.; Ready, Sean T.; Liu, Ying; Lastra, Guido; Chockalingam, Anand; Winn, Nathan C.; Clart, Laura; Kanaley, Jill A. (Frontiers in Endocrinology, 2020)
During exercise, there is coordination between various hormonal systems to ensure glucoregulation. This study examined if hypoglycemia occurs during moderate-intensity exercise in non-obese and obese individuals with and without type 2 diabetes (T2D). Eighteen non-obese, 18 obese and 10 obese with T2D were recruited. Each subject completed 2 study days that included a standard meal at 1800-h followed by rest (NOEX) or exercise (PMEX; 45 min at 55% of VO2max 2-h post meal). Glucose, insulin and glucagon concentrations were measured throughout this 5.5-h period. Subjects with T2D had elevated glucose responses to the meal on both study days, compared to non-obese and obese subjects (P<0.05). During exercise on PMEX, subjects with T2D had a greater drop in glucose concentration (-98.4±13.3 mg/dL) compared to obese (-44.8±7.1 mg/dL) and non-obese (-39.3±6.1 mg/dL; P<0.01) subjects. Glucose levels decreased more so in females than males in both conditions (P<0.01). Nadir glucose levels <70 mg/dL were observed in 33 subjects during NOEX and 39 subjects during PMEX. Obese males had a larger exercise-induced insulin drop than obese females (P=0.01). During PMEX, peak glucagon concentrations were elevated compared to NOEX (P<0.001). Male participants with T2D had an increased glucagon response during NOEX and PMEX compared to females (P<0.01). In conclusion, in sedentary individuals there is a dramatic drop in glucose levels during moderate-intensity exercise, despite appropriate insulin concentrations prior to exercise, and glucagon levels rising. Moderate-intensity exercise can lower exercise glucose concentrations below 60 mg/dL, and many individuals will be asymptomatic.